Art in Occupational Therapy Education: An Exploratory Mixed-Methods Study of an ArtsBased Module - Susan Coppola; Adrienne F. Miao; Carolyn Allmendinger; Wanqing Zhang (Scholarworks @ WMU, 2017)
Art-based learning experiences have demonstrated a range of benefits, including improved observation skills and perspective taking. This article describes the effects of an art-based module in an entry-level curriculum for occupational therapy (OT) students. An exploratory pilot study investigated the feasibility of a groupadministered visual art-based module for 20 first-year OT graduate students. Outcomes were evaluated using a mixed-methods approach that combined pre-post quantitative results from survey questionnaires and qualitative reflective essays. Pre- and post-surveys revealed significant changes in the students' perception regarding the benefits of art in OT curricula. The students' reflective essays on their learning described artbased sessions as: (a) opportunities to practice perspective shifting, (b) tapping into emotion, (c) exemplars of the therapeutic encounter, (d) integrative and "out of the box," and (e) impacting student roles and the classroom environment. Findings support art-based pedagogies to complement coursework to build an understanding of clients, creative thinking, and valued learning experiences. Learning partnerships between occupational therapy faculty, art museum educators, and artists can offer fruitful interdisciplinary learning experiences.